2018
DOI: 10.1590/s0102-053620180108
|View full text |Cite
|
Sign up to set email alerts
|

Residual effect of organic fertilization on radish production

Abstract: This research aimed to evaluate the residual effect of doses of organic compost on the radish production, as well as its effect on soil chemical properties. Experiments were conducted in two areas ("low" and "high" soil fertility). Prior to this, these areas were first used to evaluate the influence of organic compost doses on endive production. After harvesting endive, radish seeds were sown into the same plots used for endive to evaluate the residual effect. The six treatments consisted of organic compost do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
(12 reference statements)
1
11
0
7
Order By: Relevance
“…A possible explanation for this that is the inspiring effect of both mineral and organic manure fertilizers on root morphology is probably linked to soil physicochemical properties (sufficient nutrient availability, maintained soil moisture content) (Tables 4 and 5), that delay root senescence due to the slow and regular release of nutrients from manure across growth, thus ultimately improving root growth and activity in the present study. Similarly, a previous study reported that manure fertilization can enhance soil physicochemical properties and the conservation of nutrients and promote plant growth by improving root morphological traits [70].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A possible explanation for this that is the inspiring effect of both mineral and organic manure fertilizers on root morphology is probably linked to soil physicochemical properties (sufficient nutrient availability, maintained soil moisture content) (Tables 4 and 5), that delay root senescence due to the slow and regular release of nutrients from manure across growth, thus ultimately improving root growth and activity in the present study. Similarly, a previous study reported that manure fertilization can enhance soil physicochemical properties and the conservation of nutrients and promote plant growth by improving root morphological traits [70].…”
Section: Discussionmentioning
confidence: 87%
“…N recovery was higher in the late season than early under combined CM or PM with urea in the present study. This may be due to organic manure fertilization having a residual effect on later crops [70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the use of different substrates in the seedlings production still needs studies, as observed by Oliveira et al [25], who did not find significant results for the use of an organomineral fertilizer plus soil as the substrate in the production of radish seedlings. Linhares et al [26] studied doses of jitirana (5.4; 8.8; 12.2 and 15.6 t ha-1 on dry basis) and decomposition times (0, 10, 20 and 30 days before sowing), concluding that the residual effect of the higher dose (15.6 t ha-1) at the longest period (30 days) was the one that provided the greatest number of leaves (7.5 leaves) and root diameter (4.38 cm) on radish [27]. Regarding the influence of the packing type in the fresh mass of radish aerial part, packing 1 provided the highest averages for substrates S1, S4 and S3 (0.56, 0.96 and 0.75 g seedling -1 , respectively), differing from S2 (0.15 g seedling -1 ).…”
Section: Resultsmentioning
confidence: 94%
“…Entretanto, não há clareza em relação aos possíveis efeitos sinérgicos ou inibitórios da mistura da fração orgânica com fertilizantes minerais bem como a participação e influência de cada um desses compartimentos no fornecimento adequado de nutrientes para as plantas. (CUNHA et al, 2015;LYNCH, 2015;LANNA et al, 2018).…”
Section: Aspectos De Fertilidade Relacionados a Fertilizantes Organomunclassified